Compositional depths of cognitive semantics: bridging perceptual experiences and conceptual structures - Pala, Kiran; Nedumpozhimana, Vasudevan; Shalu, S. (Frontiers in Psychology, 2025)
The primary aim of this research was to investigate the intricate relationship between the structural elements of experiences and their essential role in meaning formation. The analysis focused on understanding the nature of mental representations and the subjective, phenomenal qualities that emerge within experiences. To achieve this, an integrated approach, combining cognitive semantics with phenomenological analysis, was employed to examine the compositional complexities of the dynamic interaction between a priori and immediate experiences and their significance in meaning formation. The study highlights the interconnectivity of structural elements within experience as a critical factor in shaping the phenomenal qualities of mental representations. Another key contribution of this study is the introduction of the “fulfiller” concept, which underscores the importance of absent qualities in meaning formation-an often-overlooked aspect in traditional models that focus solely on present attributes. The “fulfiller” concept emphasizes how absence, in addition to presence, influences meaning assignment. This inclusion enhances our understanding of meaning formation by considering both the tangible and intangible dimensions of the experiential-intentional process, offering a more comprehensive framework for understanding how meaning emerges from the complex interaction of present and absent qualities.